Maternal Nanos represses hid/skl-dependent apoptosis to maintain the germ line in Drosophila embryos. - Sato, K.; Hayashi, Y.; Ninomiya, Y.; Shigenobu, S.; Arita, K.; Mukai, M.; Kobayashi, S. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Nanos (Nos) is an evolutionarily conserved protein essential for the survival of primordial germ cells. In Drosophila, maternal Nos partitions into pole cells and suppresses apoptosis to permit proper germ-line development. However, how this critical event is regulated by Nos has remained elusive. Here, we report that Nos represses apoptosis of pole cells by suppressing translation of head involution defective (hid), a member of the RHG gene family that is required for Caspase activation. In addition, we demonstrate that hid acts in concert with another RHG gene, sickle (skl), to induce apoptosis. Expression of skl is induced in pole cells by maternal tao-1, a ste20-like serine/threonine kinase. Tao-1-dependent skl expression is required to potentiate hid activity. However, skl expression is largely suppressed in normal pole cells. Once the pole cells lack maternal Nos, Tao-1-dependent skl expression is fully activated, suggesting that skl expression is also restricted by Nos. These findings provide the first evidence that the germ line is maintained through the regulated expression of RHG genes.